Status of tigers, co-predators, and prey in India - Jhala, Y. V.; Gopal, Rajesh; Qureshi, Q. (Qamar) (National Tiger Conservation Authority, Ministry of Environment & Forests, and Wildlife Institue of India, Dehradun, 2008)
Report of a project commenced by the National Tiger Conservation Authority in collaboration with Wildlife Institute of India in 2003.